Fostering Academic Engagement in Post-graduate Students: Assessing the Role of Positive Emotions, Positive Psychology, and Stress - Saleem, Muhammad Shoaib; Isha, Ahmad Shahrul Nizam; Awan, Maheen Iqbal; Yusop, Yuzana Binti; Naji, Gehad Mohammed Ahmed (Frontiers in Psychology, 2022)
This study assessed the relationship between positive emotions, psychological capital, and study engagement behaviour with the moderated effect of stress amongst postgraduate students in Malaysia. A sample of 373 postgraduate students registered in different academic domains were obtained in different states of Malaysia via a self-administered questionnaire. We used the structural equation modelling (SEM) technique, which assessed the confirmatory factor analysis, reliability analysis, validity analysis, measurement, and structural models as well as the path analysis. Further, the (5000) bootstrapping technique was used to test the final model for robust results. All our measurement indices were well under the limit. Whereas for the hypothesized model, our results confirmed that positive emotions had a positive and significant effect on students’ psychological capita as well as on their study engagement behaviour. Further, PsyCap also had a positive and significant effect on study engagement behaviour. Our results also reported the deteriorating negative effect of stress between PsyCap and the academic engagement of students. The findings of the study conform to the theoretical notions that positive emotions help individuals to build on their cognitive resources, which in turn will help them to cope with their engagement behavioral requirements. Nonetheless, the stress exerted through their study demands may deter their psychological resource, thus negatively affecting their engagement behaviour. Interventions like personal coaching/counselling, appropriate follow-up, and flexible goal settings with other measures may help postgraduate students in achieving their daunting tasks.